Draft Annual Plan 2003-2004 Sikkim State - Planning Commission (Planning Commission, 2003)
Sikkim strategically located with international borders on its North, East & West borders is a jewel in the crown of India. Its scenic natural flora, fauna, vegetation, ethnic communities and rich culture steeped in traditions adds to its uniqueness. the special status under Article 371(F), a special category State with 90% grant and 10% loan and with the recent formal approval being accorded as a Member of the North Eastern Council has given the State and the local inhabitants a sense of pride, security and oneness with the Indian Union. the achievements of the 9th Plan along with the drawbacks has been assessed.
Planning and Development Department, Government of Sikkim